Endovascular Recanalization for Symptomatic Subacute to Chronic Atherosclerotic Basilar Artery Occlusion - Zhao, Wei; Zhang, Jinping; Song, Yun; Sun, Lili; Zheng, Meimei; Yin, Hao; Zhang, Jun; Wang, Wei; Han, Ju (Frontiers in Neurology, 2019)
Background: The prognosis is poor for patients with symptomatic subacute to chronic atherosclerotic basilar artery occlusion (BAO) refractory to medical therapy. There has been no consensus on the optimal treatment for these patients until now. Objectives: To assess the feasibility of endovascular recanalization for patients with symptomatic subacute to chronic atherosclerotic BAO refractory to medical therapy. Methods: Consecutive patients who underwent endovascular recanalization for symptomatic subacute to chronic symptomatic atherosclerotic BAO from May 2015 to October 2018 were enrolled in our stroke center. Demographic, clinical, angiographic, procedural and follow-up data were collected and analyzed. Results: Twenty-one patients were enrolled in this study (mean age 57.9 years; 90.5% male; median pretreatment National Institutes of Health Stroke Scale (NIHSS) score 10; median time from image-documented BAO to treatment 15 days). The success rate of the procedure was 81.0% (17/21). Periprocedural perforator strokes occurred in 2 patients (9.5%, 2/21). At 90 days, there was one death due to pneumonia (unrelated to the procedure), and there were no recurrent cases of TIA or stroke in the other 16 patients. At 90 days, 76.5% (13/17) of patients achieved a good clinical outcome (mRS: modified Rankin Scale (mRS) score 0-2), and 94.1% (16/17) of patients achieved an acceptable outcome (mRS score 0-3). During the 17.4±8.0-month clinical follow-up period, one patient suffered from Wallenberg syndrome at 29 months. Conclusions: Our study suggests that endovascular recanalization for subacute to chronic symptomatic atherosclerotic BAO appears to be feasible in selected patients.